An examination of contemporary works for wind band and chamber ensemble: Cajun Folk Songs by Frank Ticheli, Elegy by Travis Cross, and Symphony for Brass and Percussion by Alfred Reed - Rajewski, Benjamin Peter (My University, 2025)
The following report provides a comprehensive analysis of two works for wind band and one chamber work for brass and percussion: Cajun Folk Songs by Frank Ticheli, Elegy by Travis Cross, and Symphony for Brass and Percussion by Alfred Reed. This analysis provides information necessary for the rehearsal preparation and performance for a conductor. This analysis provides biographical information about the composers, details of each composition, and a historical perspective of the works themselves. Detailed are the technical difficulties, stylistic concerns, musical elements, and form and structure of each composition. Included in this document are a music education mission statement and perspective on quality literature selection. Suggested listening, seating charts, acoustical justifications, and rehearsal plans are provided. The contents of this analysis will inform conductors as they prepare the musical and educational decisions used in rehearsal and the performance of these works.
Keywords: Wind band literature; Frank Ticheli; Alfred Reed; Dr. Travis Cross; Score analysis; Music education